Unipolar Switching in Pt/GeSexTe1-x/Pt - Jeong, Doo Seok; Son, Seo Hee; Lee, Suyoun; Cheong, Byung-Ki (ELECTROCHEMICAL SOC INC, 2010)
We report unipolar switching in amorphous GeSexTe1-x of varying Se content (x) sandwiched between Pt top and bottom electrodes. After the initialization process, termed electroforming, repeatable unipolar switching was observed. We investigated the effect of the Se to Te ratio on the unipolar switching as well as on the electroforming voltage and the resistance of the as-electroformed state, which showed increases in the electroforming voltage and the resistance of the as-electroformed state with increasing Se content. Some phenomenological evidences of unipolar switching, which cannot be explained by means of the conventional phase-change effect, are reported. (C) 2010 The Electrochemical Society. [DOI: 10.1149/1.3501971] All rights reserved.